(untitled) (Bangladesh Journal of Pharmacology, 2016)
Leaf juices as well as leaves of Barleria prionitis and Barleria grandiflora are being used by rural people across various regions of India in the treatment of oral ailments such as dental troubles, gum ailments, pyorrhoea, dental carries and mouth ulcers. Zone of inhibition and MIC values obtained for all the extracts suggest ethanolic extract of the herbs were more antimicrobial when compared to the aqueous extract. Results of biofilm suppression were found statistically significant (p<0.05) when compared to control. Cytotoxicity was evaluated by MTT assay on human gingival fibroblast and human dermal fibroblast cell lines for ethanolic extract of the herbs. CTC50 value was found to be more than 1,000 µg/mL for ethanolic extracts of both herbs. Chlorhexidine was found to be more cytotoxic with CTC50 value of 12.525 µg/mL. Ethanolic extract of B. prionitis and B. grandiflora found significantly cytotoxic (p<0.05) in comparison with control. Video Clip of Methodology: Cytotoxicity assay: 18 min 45 sec Full Screen Alternative